The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13102288
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Trapping in bcc Iron

Abstract: Fundamental understanding of H localization in steel is an important step towards theoretical descriptions of hydrogen embrittlement mechanisms at the atomic level. In this paper, we investigate the interaction between atomic H and defects in ferromagnetic body-centered cubic (bcc) iron using density functional theory (DFT) calculations. Hydrogen trapping profiles in the bulk lattice, at vacancies, dislocations and grain boundaries (GBs) are calculated and used to evaluate the concentrations of H at these defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 119 publications
(296 reference statements)
1
24
0
Order By: Relevance
“…[ 42,43 ] Alternatively, using Hirth's interpretation, the binding of hydrogen to a screw dislocation could be estimated to be 0.2–0.3 eV based on the shift of the γ‐peak toward lower temperatures, [ 61 ] which is in correspondence to binding energies obtained by DFT calculations. [ 41–44 ] But although the H‐CW peak in bcc iron has been investigated quite extensively, [ 42,65,66,69–78 ] only limited studies have been made linking this peak to the hydrogen trapping capacity and HE. Kikuta et al [ 79 ] observed a correlation with the height of the H‐CW peak and the decrease of the notch tensile strength for pure iron and a high‐strength steel.…”
Section: The Interaction Of Microstructural Defects With Hydrogen Revealed By Ifmentioning
confidence: 92%
See 4 more Smart Citations
“…[ 42,43 ] Alternatively, using Hirth's interpretation, the binding of hydrogen to a screw dislocation could be estimated to be 0.2–0.3 eV based on the shift of the γ‐peak toward lower temperatures, [ 61 ] which is in correspondence to binding energies obtained by DFT calculations. [ 41–44 ] But although the H‐CW peak in bcc iron has been investigated quite extensively, [ 42,65,66,69–78 ] only limited studies have been made linking this peak to the hydrogen trapping capacity and HE. Kikuta et al [ 79 ] observed a correlation with the height of the H‐CW peak and the decrease of the notch tensile strength for pure iron and a high‐strength steel.…”
Section: The Interaction Of Microstructural Defects With Hydrogen Revealed By Ifmentioning
confidence: 92%
“…For example, using the Schoeck model, the binding energy of hydrogen to mixed dislocations can be determined to be 0.3 eV, [ 69 ] which is rather similar to the values obtained by TDS [ 17,21,22,61 ] and DFT results. [ 42,43 ] Alternatively, using Hirth's interpretation, the binding of hydrogen to a screw dislocation could be estimated to be 0.2–0.3 eV based on the shift of the γ‐peak toward lower temperatures, [ 61 ] which is in correspondence to binding energies obtained by DFT calculations. [ 41–44 ] But although the H‐CW peak in bcc iron has been investigated quite extensively, [ 42,65,66,69–78 ] only limited studies have been made linking this peak to the hydrogen trapping capacity and HE.…”
Section: The Interaction Of Microstructural Defects With Hydrogen Revealed By Ifmentioning
confidence: 95%
See 3 more Smart Citations